In silico RAD-Seq as a possible tool for ancestry determination : an application in helicobacter pylori (2018)
Helicobacter pylori is a bacterium that has been associated to a diverse range of pathologies that varies from gastritis to gastric cancer. Due to its clinical an evolutionary importance, there has been extensive research focused on the population genetics among different H. pylori isolates worldwide. Until now Multilocus Sequence Typing (MSLT) has been the main method used for the determination of ancestry. However, this technique has certain limitations regarding consistency in clusterization and has been generating conflicting results. Due to the fact that a bacterium like H. pylori has a high recombination rate, a more versatile technique with a whole genome approach is desirable. Recently, with decreasing sequencing costs, full genome sequencing of small microbial genomes is becoming a viable approach. However, when typing hundreds of strains, the cost is still prohibitive. In this sense, Restriction site-associated DNA sequencing (RAD-Seq) is a cost-effective method that is suitable for phylogenetic inferences, especially in non-model organisms...